Peramalan jumlah produksi kelapa sawit di Provinsi Riau Periode Tahun 2023 - 2025 - Zevira Saffa Komara; Dewi Rohma Wati; RA. Diana Maulidah (Agrivet : Jurnal Ilmu-Ilmu Pertanian dan Peternakan (Journal of Agricultural Sciences and Veteriner), 2025)
Oil palm is one of the plantation crops that has an important role in the agricultural sector. The increasing demand for palm oil derivative products has resulted in an increase in demand for palm oil commodities. Riau Province is one of the palm oil producing provinces in Indonesia. The aim of this research is to forecast the amount of palm oil production in 2023-2025. The research method used is quantitative. The data used is secondary data in the form of data on the amount of palm oil production in Riau Province for 2018-2022. The research results show that: 1) Model (1,1,0) is the best model because it has the smallest RMSE, MAD and MAPE values; 2) The results of forecasting the amount of palm oil production in Riau Province for 2023-2025 tend to increase in each period.